Study familial hypertrophic cardiomyopathy using patient-specific induced pluripotent stem cells. (10th September 2014) - Han, Lu; Li, Yang; Tchao, Jason; Kaplan, Aaron D.; Lin, Bo; Li, You; Mich-Basso, Jocelyn; Lis, Agnieszka; Hassan, Narmeen; London, Barry; Bett, Glenna C.L.; Tobita, Kimimasa; et al.
Abstract: Aims: Familial hypertrophic cardiomyopathy (HCM) is one the most common heart disorders, with gene mutations in the cardiac sarcomere. Studying HCM with patient-specific induced pluripotent stem-cell (iPSC)-derived cardiomyocytes (CMs) would benefit the understanding of HCM mechanism, as well as the development of personalized therapeutic strategies. Methods and results: To investigate the molecular mechanism underlying the abnormal CM functions in HCM, we derived iPSCs from an HCM patient with a single missense mutation (Arginine442Glycine) in the MYH7 gene. CMs were next enriched from HCM and healthy iPSCs, followed with whole transcriptome sequencing and pathway enrichment analysis. A widespread increase of genes responsible for 'Cell Proliferation' was observed in HCM iPSC-CMs when compared with control iPSC-CMs. Additionally, HCM iPSC-CMs exhibited disorganized sarcomeres and electrophysiological irregularities. Furthermore, disease phenotypes of HCM iPSC-CMs were attenuated with pharmaceutical treatments. Conclusion: Overall, this study explored the possible patient-specific and mutation-specific disease mechanism of HCM, and demonstrates the potential of using HCM iPSC-CMs for future development of therapeutic strategies. Additionally, the whole methodology established in this study could be utilized to study mechanisms of other human-inherited heart diseases.